2016
DOI: 10.1177/0961203316682095
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-OH vitamin D level in treatment-naïve systemic lupus erythematosus patients: Relation to disease activity, IL-23 and IL-17

Abstract: Objectives The aim of this study was to assess the vitamin D status in treatment-naïve SLE patients and its association with clinical and laboratory markers of disease activity, including serum levels of IL-17 and IL-23. Methods Fifty-seven treatment-naïve SLE patients along with 42 matched controls were included. SLEDAI score was used to estimate disease activity. Serum levels of 25(OH) D, IL-17 and IL-23 were measured. Results The median level of 25(OH) D in SLE patients (40.8; 4-70 ng/ml) was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 48 publications
(69 reference statements)
2
36
0
Order By: Relevance
“…In order to detect the source of heterogeneity, a subgroup analysis was conducted. Previous studies revealed that 25(OH)D levels were not significantly correlated with age and disease duration in SLE patients; subgroup analysis revealed that, compared with healthy controls, 25(OH)D levels were significantly reduced in both juvenile SLE patients (age < 18 years) and adult SLE patients (age ≥ 18 years), and in both SLE patients of duration <5 years and ≥5 years, indicating no matter the changes of age and disease duration, the 25(OH)D levels of SLE patients were significantly reduced.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In order to detect the source of heterogeneity, a subgroup analysis was conducted. Previous studies revealed that 25(OH)D levels were not significantly correlated with age and disease duration in SLE patients; subgroup analysis revealed that, compared with healthy controls, 25(OH)D levels were significantly reduced in both juvenile SLE patients (age < 18 years) and adult SLE patients (age ≥ 18 years), and in both SLE patients of duration <5 years and ≥5 years, indicating no matter the changes of age and disease duration, the 25(OH)D levels of SLE patients were significantly reduced.…”
Section: Discussionmentioning
confidence: 75%
“…Ultimately, 19 studies were included in our meta‐analysis (Figure ). Sixteen studies compared circulating 25(OH)D levels between SLE patients and healthy controls (Table ); seven Studies provided the information about the deficiency, insufficiency, sufficiency of vitamin D in both SLE patients and healthy controls (Table ); 6 studies explored the correlations between disease activity of SLE and 25(OH)D levels (Table ). The NOS scores of included studies ranged from 6 to 8 stars, indicating each of the studies had high methodological quality (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, a number of larger-scale case-control studies confirmed the relationship between hypovitaminosis D and the prevalence of SLE [75,76,77,78], particularly in patients with lupus nephritis [75]. In our recent age- and gender-matched case-control study of 61 SLE patients and 61 healthy controls, we found that a deficiency of the total 25(OH)D 3 level, as measured by liquid chromatography-tandem mass spectrometry, was significantly more prevalent in the patient group (19.7% vs. 3.3%, p = 0.003) [79].…”
Section: Hypovitaminosis D and Its Impact On Disease Activity And mentioning
confidence: 99%